PROSPECTS FOR IMPROVING FINANCIAL LITERACY - Salokhiddinov Jaloliddin Ulugbek ugli; Raufov Kuvonchbek Husin ogli (European Science Publishing, 2024)
Financial literacy is essential for individuals to make informed decisions, manage personal finances effectively, and contribute to economic stability. Despite its importance, financial literacy levels remain low globally, necessitating comprehensive strategies for improvement. This paper explores the current state of financial literacy, identifies key challenges, and examines innovative approaches to enhance financial education. We analyze various educational initiatives, technological advancements, and policy interventions aimed at increasing financial literacy. Special attention is given to the role of digital tools, gamification, and personalized learning experiences in making financial education more accessible and engaging. The impact of these strategies on different demographic groups, including youth, adults, and underserved communities, is assessed. Our findings suggest that a multifaceted approach, integrating formal education, community programs, and digital platforms, holds significant promise for advancing financial literacy. Effective collaboration among governments, educational institutions, financial organizations, and technology providers is crucial to realizing these prospects. The paper concludes with recommendations for policymakers and educators to foster a financially literate society, thereby enhancing individual well-being and economic resilience.
Keywords: Financ bank, loan, deposit, profit, currency, exchange, foreign capital, income, interest rates, plastic cards, factoring services, business, budget.